2015
DOI: 10.1371/journal.pone.0130542
|View full text |Cite
|
Sign up to set email alerts
|

Functional Expression and Characterization of Schizosaccharomyces pombe Avt3p as a Vacuolar Amino Acid Exporter in Saccharomyces cerevisiae

Abstract: In Saccharomyces cerevisiae, Avt3p and Avt4p mediate the extrusion of several amino acids from the vacuolar lumen into the cytosol. SpAvt3p of Schizosaccharomyces pombe, a homologue of these vacuolar amino acid transporters, has been indicated to be involved in spore formation. In this study, we confirmed that GFP-SpAvt3p localized to the vacuolar membrane in S. pombe. The amounts of various amino acids increased significantly in the vacuolar pool of avt3Δ cells, but decreased in that of avt3 +-overexpressing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 42 publications
3
12
1
Order By: Relevance
“…Although we do not exclude the possibility that the vacuolar contents of these amino acids were indirectly affected in the avt3Δavt4Δ cells, export assays of 14 C-labeled amino acids using isolated vacuolar membrane vesicles suggested that several neutral amino acids examined were the transport substrates of AtAvt3A as well as Avt3. Furthermore, our mutational studies using AtAv-t3A E241A revealed that a Glu residue conserved in plant and yeast is critical for its transport activity as similarly demonstrated for the fission yeast Avt3 [30]. These results suggested that AtAVT3-related genes are the functional homologs of AVT3/AVT4.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Although we do not exclude the possibility that the vacuolar contents of these amino acids were indirectly affected in the avt3Δavt4Δ cells, export assays of 14 C-labeled amino acids using isolated vacuolar membrane vesicles suggested that several neutral amino acids examined were the transport substrates of AtAvt3A as well as Avt3. Furthermore, our mutational studies using AtAv-t3A E241A revealed that a Glu residue conserved in plant and yeast is critical for its transport activity as similarly demonstrated for the fission yeast Avt3 [30]. These results suggested that AtAVT3-related genes are the functional homologs of AVT3/AVT4.…”
Section: Discussionsupporting
confidence: 69%
“…In contrast to the vesicles with AtAvt3A, in which the level of 14 C-Ala rapidly decreased upon the addition of ATP, 14 C-Ala was accumulated in vesicles with AtAvt3A E241A in the presence of ATP (Fig. 5C), in a similar manner to that observed for the fission yeast Avt3 E469A [30]. 14 C-Pro preloaded in the vacuolar membrane vesicles of the avt3Δavt4Δ cells immediately decreased in an ATP-dependent manner by the expression of AtAvt3A but not AtAvt3A E241A (Fig.…”
Section: Conserved Glutamate Residue Glu 241 Is Critical For the Transupporting
confidence: 71%
“…Consistent with previous studies (Chardwiriyapreecha et al, 2015;Russnak et al, 2001;Tone et al, 2015a, b), our fluorescent microscopic observations confirmed that GFP-fused Avt1, Avt3, and Avt7 expressed under the control of a constitutive ADH1 promoter were mainly located on the vacuolar membrane, as well as in the endoplasmic reticulum (ER; cortical ER and nuclear envelope) to a lesser extent, in SD medium (Fig. 7).…”
Section: Fig 4 Cytosolic and Vacuolar Amino Acid Contents Of Strainsupporting
confidence: 93%
“…Since the in vitro ATP-dependent activity of 14 C-labelled proline efflux at the vacuolar membrane has been already detected (Ishimoto et al, 2012), it should be further determined whether Avt3 is fully responsible for this activity. Our result does not conflict with a finding in Schizosaccharomyces pombe that the SpAvt3 protein, an ortholog of Avt3 and Avt4, mediates the vacuolar export of proline and other various amino acids (Chardwiriyapreecha et al, 2015).…”
Section: Fig 4 Cytosolic and Vacuolar Amino Acid Contents Of Straincontrasting
confidence: 62%
“…Homologs in Schizosaccharomyces pombe Few homologous genes of vacuolar amino acid transporters are found in the genome of S. pombe (Table 1), which imply less redundancy among their functions, and so S. pombe is expected to be advantageous for clarifying the physiological roles of vacuolar amino acid transporters. Mukaiyama et al 31) indicated that S. pombe Avt3 (SpAvt3) is involved in spore formation under starvation condition. We observed that vacuolar amino acid contents were greatly increased in S. pombe avt3∆ mutant and were decreased by the overexpression of avt3 + gene, indicating that SpAvt3 is involved in the export of vacuolar amino acids and important for amino acid compartmentalization in S. pombe cells.…”
Section: Pq-loop Proteinsmentioning
confidence: 99%